Educational Management of Effleurage Massage Therapy with Virgin Coconut Oil for Families of Stroke Patients - Carissa Muthia Putri Nugroho; Ati Surya Mediawati (Universitas Duta Bangsa Surakarta, 2026)
Introduction: Effleurage massage therapy using virgin coconut oil (VCO) shows promise in preventing pressure ulcers in stroke patients by improving circulation and skin health. Objectives: This study aims to determine the application of effleurage massage therapy education with VCO on the knowledge of families caring for stroke patients in the HCU room of one of the highest referral hospitals in West Java. Method: A descriptive exploratory case study involved physical assessments, interviews, and direct observations. Participants completed a pre-test questionnaire, followed by a post-test after the educational intervention. Data were analyzed using the 3M approach. Results: The Man aspect shows that there are 30 nurses, and none of them have massage therapy expertise. The Method aspect shows that effleurage massage therapy with VCO has not been implemented. The material aspect shows that VCO is not yet available in the room. There was a significant increase in the knowledge score of the family, from an initial score of 40 to 100 after the intervention. Conclusion: Providing education on effleurage massage therapy with VCO to families of stroke patients is effective in increasing family knowledge about massage therapy.